Communicating Bronchopulmonary Foregut Malformation Type III with Pulmonary Sequestration Diagnosed in a Newborn: A Case Report - Su Kyung Kim; Jin Wha Choi; Hong Kwan Kim; Se In Sung; Yun Sil Chang; Won Soon Park (Korean Society of Neonatology, 2019)
Communicating bronchopulmonary foregut malformation (CBPFM) is a communication between the respiratory and gastrointestinal tracts that can be difficult to differentiate from pulmonary sequestration or H-type tracheoesophageal fistula (TEF) because of the similarities in clinical features. A female neonate born at full term had been experiencing respiratory difficulty during feeding from the third day of life. The esophagography performed to rule out H-type TEF revealed that the esophageal bronchus directly communicated with the left lower lobe (LLL) of the lung. Lobectomy of the LLL, fistulectomy of the esophagobronchial fistula, and primary repair of the esophagus were performed. Finally, CBPFM type III with pulmonary sequestration was confirmed on the basis of the postoperative histopathological finding. We report the first newborn case of CBPFM type III with pulmonary sequestration in Korea.